Continuum-scale modeling of helium bubble bursting under plasma-exposed tungsten surfaces. (5th November 2018) - Blondel, Sophie; Bernholdt, David E.; Hammond, Karl D.; Wirth, Brian D.
Abstract: We present a comparison between a continuum-scale drift-diffusion-reaction cluster dynamics prediction of helium retention in low-energy helium plasma exposed tungsten and experimental measurements, in a temperature regime that did not produce tungsten fuzz. Our cluster dynamics model, Xolotl, has been successfully benchmarked to high helium implantation flux MD simulations at relatively low implanted fluence. In this article, we also describe the extension of the Xolotl DDR model to incorporate the effect of bubble bursting, which is observed in very high rate MD simulations, as well as MD simulations at longer times than simulated in our prior benchmarking comparison. The bursting model parameters have been tuned by comparing to MD simulations at a flux of 5.0 × 10 27 m −2 s −1, and also compared to lower implanted fluence simulations performed at 4.0 × 10 25 m −2 s −1 . This article then reports on the consistency of the Xolotl predictions with respect to the size of the simulated cluster phase space (i.e. the maximum cluster size), initial vacancy concentration, and bubble growth trajectory (maximum number of helium atoms per vacancy). Finally, our simulation results are compared to helium plasma experiments that did not produce fuzz. While the Xolotl predictions including bubble bursting are in quantitative agreement with high-flux MD simulations, the initial comparison to plasma exposure experiments at a flux on the order of 10 21 m −2 s −1 disagree by more than an order of magnitude, and in fact cannot reproduce the trends in helium retention with varying exposure temperature. Modifying the initial vacancy concentrations and helium cluster diffusion behavior in Xolotl leads to a reasonable agreement with the experimental observations, although the underlying physical explanation for these modifications remains unclear. The predicted helium content at experimentally relevant fluxes has been shown to be relatively insensitive to the parameters used in the bubble bursting model implemented in Xolotl, although these parameters have a larger influence at higher flux. More systematic comparisons between the modeling predictions with both experiments and MD simulation results is expected to improve the bubble bursting model in Xolotl in the future.